Studies in environment and development - Singh, Ram Bali. (New Delhi, India : Rakesh Prakashan, 1988)
Contributed articles.
Includes bibliography.
Keywords: Environmental policy -- India; Environmental policy -- Developing countries; Economic development -- Environmental aspects; Environmental policy; India -- Economic policy -- 1947- -- Environmental aspects; Developing countries -- Economic policy -- Environmental aspects